PERAN PARENTAL ATTACHMENT TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI DI RA HAYATUN THOYYIBAH - Sekar Ayu Lestari; M. Syukri Azwar Lubis; Reni Khairani (Fakultas Agama Islam Universitas Al Washliyah, 2025)
The role of parents is crucial in early childhood development, especially in shaping social-emotional aspects. Attachment between parents and children plays a vital role in fostering a sense of security, self-confidence, and the ability to establish healthy social relationships. Proper parenting can help shape children's character, allowing them to grow into moral and dignified individuals. A lack of attachment, as seen in broken home families, can negatively impact children's social-emotional development. This study aims to examine how parental attachment influences the social-emotional development of early childhood students at RA Hayatun Thoyyibah. Understanding this relationship is expected to provide insights for parents and educators in optimizing parenting strategies that support children's social-emotional growth.